Thailand Economic Monitor, April 2018 : Beyond the Innovation Paradox - World Bank Group (World Bank, Washington, DC, 2018)
The global economy grew at an estimated 3.0 percent in 2017, slightly above expectations in mid-year, with synchronous recovery in advanced economies and emerging markets and developing economies. Thailand has continued to make progress in reducing poverty. Thailand’s economic recovery is expected to accelerate in 2018, with growth projected at 4.1 percent, driven by external demand and private consumption. Thailand is an example of an emerging market facing the innovation paradox: returns to R&D are high but actual investments are low compared to peers.